A companion to Old and Middle English literature - Lambdin, Laura C.; Lambdin, Robert T. (Greenwood Press, 2002)
Defines, classifies, and critically studies Old and Middle English literature according to genres. Old and Middle English literature can be obscure and challenging and has elicited a large body of criticism. Readers confronting medieval literature soon note that writers of the era were masters of literary form. Indeed, many works draw on similar texts, since imitation was admired. Recent scholarship, too, has given much attention to the importance of genre, since the genre in which a work is written often conveys knowledge of the author's intentions and thus helps illuminate the meaning of the.